(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
هدفت هذه الدّراسة لتحديد آليات تنمية رأس المال البشري في جامعة تشرين، ودورها في إعادة إعمار سورية، ومدى تطبيق جامعة تشرين لهذه الآليات وللأهداف الاستراتيجية المحددة في خطة التعليم العالي، وقد قام الباحث بتوزيع استبيان على 335 فرد من أعضاء الهيئة التعليمية في جامعة تشرين، وقد خلصت الدّراسة إلى أنّ اتباع الجامعات لهذه الآليات من شأنها الإسهام في إعادة الإعمار. ثمّ قدّم ملخّصاً لأهمّ النتائج التي تمّ التوصّل إليها، حيث كانت النتيجة الرئيسة الأهمّ هي عدم تطبيق جامعة تشرين لآليات تنمية رأس المال البشري والأهداف الاستراتيجية بالشكل المطلوب، وأن هناك ضعف اهتمام بالبحث العلمي وغياب الخطط وضعف الميزانية المخصصة والحاجة الملحة لقواعد البيانات ومحركات البحث العلمية. This study aimed at identifying Mechanisms of Human Capital Development in Tishreen University, and its role in reconstruction of Syria. In addition, the extent Tishreen University applied these mechanisms and the strategic objectives identified in the Higher Education Plan. The researcher gave a questionnaire to 335 people, they are members of the Teaching Staff in Tishreen University, the main result of the study was that the universities follow to these mechanisms will contribute in Reconstruction. We have provided a summary of the main result that have found out is that Tishreen University did not apply mechanisms of Human Capital Development and the strategic objectives as required, and there is no interest in scientific research, absence of research plans and weak budget, and a dire need to contract with scientific data and research engines.